Revolutionizing Marketing with Generative AI - Tomminen, Valtteri (2025)
Generative AI has become widespread in recent years and is increasingly being used in marketing. The phenomenon is relatively new to marketers and sales professionals, and it has not been studied much. However, the interest in the use of Generative AI in marketing has exploded in the last few years, demonstrating the relevance and importance of the topic.